Synopsis of the Castniidae (Lepidoptera) from Honduras and Nicaragua, Central America - van Den Berghe, Eric; Maes, Jean-Michel; Hernández-Baz, Fernando; González, Jorge M. (Zootaxa, 2020)
We present a catalog of nine taxa of Castniidae reported for Nicaragua and Honduras including Prometheus zagraea salvina, a first record for Nicaragua. We also include general and field observations of behavior to help explain why members of this family are poorly represented in collections.